2012
DOI: 10.1364/oe.20.008284
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate resolution for refractometric sensing with whispering gallery mode microcavities

Abstract: Many proposed microfluidic biosensor designs are based on the measurement of the resonances of an optical microcavity. Fluorescence-based resonators tend to be simpler and more robust than setups that use evanescent coupling from tuneable laser to probe the cavity. In all sensor designs the detection limits depend on the wavelength resolution of the detection system, which is a limitation of fluorescence-based devices. In this work, we explore the ultimate resolution and detection limits of refractometric micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 33 publications
(46 reference statements)
2
35
0
Order By: Relevance
“…Indeed, the resonance spectra measured here (shown later in Fig. 6) exhibit peaks skewed to short λ , a result of cylindrical resonator skew rays [12,25]. Nonetheless, as shown in § 4, the β = 0 resonances from Eq.…”
Section: Resonances and Mode Theorysupporting
confidence: 49%
“…Indeed, the resonance spectra measured here (shown later in Fig. 6) exhibit peaks skewed to short λ , a result of cylindrical resonator skew rays [12,25]. Nonetheless, as shown in § 4, the β = 0 resonances from Eq.…”
Section: Resonances and Mode Theorysupporting
confidence: 49%
“…50 nm/RIU, the detection limits for heavy oils are on the order of 10 À4 RIU, assuming 10 pm spectral resolution is achievable via Fourier methods [28]. The results show that this sensor structure can be used for viscous heavy oils.…”
Section: Discussionmentioning
confidence: 86%
“…Unfortunately, there is no function that will fit a distribution of overlapping Lorentzians from the spiraling WGMs. In previous work 16 we suggested that a skewed Lorentzian 17 would give a better fit:…”
Section: Discussionmentioning
confidence: 97%